Theoretical and Numerical Studies of Elastic Buckling and Load Resistance of a Shuttle-Shaped Double-Restrained Buckling-Restrained Brace - Jun Shi; Shuangshuang Jin; Lueqin Xu; Yangqing Liu; Ruijie Zhang (Buildings, 2023)
A new type of shuttle-shaped double-restrained buckling-restrained brace (SDR-BRB) is proposed, which adopts the form of a shuttle-shaped deformation section similar to its bending moment distribution as the external restraining system. The SDR-BRB has the advantages of superlong size, high load-carrying capacity, and lightweight components, and is suitable for use in large-span spatial structures and bridge structures with an exposed BRB. First, the calculation formula of the elastic buckling load of a pin-ended SDR-BRB is derived based on the equilibrium method, which is verified through the eigenvalue buckling analysis method, and the effects of the main geometric parameters on its elastic buckling behavior are evaluated. The effects of multiple key factors on the load-carrying capacity of the SDR-BRB are then studied by parametric analysis. The results show that the restraining ratio, initial imperfection, and gap have significant effects on the ultimate load-carrying capacity and overall stability of the SDR-BRB, while the effect of the diameter–thickness ratio is relatively small. On this basis, the fitting formula of the critical restraining ratio of the SDR-BRB considering the influences of initial imperfection and gap is proposed and verified by finite element analysis. The research lays a foundation for further research into the elastic–plastic hysteretic behavior and design method of an SDR-BRB.